2022
DOI: 10.1111/jch.14438
|View full text |Cite
|
Sign up to set email alerts
|

Day‐to‐day blood pressure variability in COVID‐19: A biomarker of disrupted central autonomic network

Abstract: He and coworkers 1 provides several new insights into the significant relationships of day-to-day systolic blood pressure (SBP) variability, that is, standard derivation (SD), coefficient of variation (CV), and variability independent of mean (VIM)-with acute respiratory distress syndrome (ARDS) and mortality in 702 COVID-19 patients with hypertension. In addition, increased blood pressure (BP) variability was associated with severe inflammation and myocardial injury. 1 In COVID-19, systemic inflammation, 2 en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…It is, however, well understood that elevated sympathetic activity (and parasympathetic hypoactivity), hyperglycaemia and immune-dysregulation are markers of a poor outcome; and potential pathophysiological mechanisms underlying this relationship have been identified. [79][80][81][82][83][84] If confirmed by carefully-planned prospective studies, these insights may help to prevent an unfavourable outcome of the disease; and they may also explain the conundrum of bio-social disparities in the prognosis of COVID-19. [85][86][87] F I G U R E 2 Physiological macroscopic multi-compartment and multi-level model of the organismic response to respiratory virus infection, along with stages of the viral invasion process, with conditions and reactions associated with affected compartments (modified from Tretter et al).…”
Section: Dynamic Equilibrium Modelsmentioning
confidence: 89%
See 1 more Smart Citation
“…It is, however, well understood that elevated sympathetic activity (and parasympathetic hypoactivity), hyperglycaemia and immune-dysregulation are markers of a poor outcome; and potential pathophysiological mechanisms underlying this relationship have been identified. [79][80][81][82][83][84] If confirmed by carefully-planned prospective studies, these insights may help to prevent an unfavourable outcome of the disease; and they may also explain the conundrum of bio-social disparities in the prognosis of COVID-19. [85][86][87] F I G U R E 2 Physiological macroscopic multi-compartment and multi-level model of the organismic response to respiratory virus infection, along with stages of the viral invasion process, with conditions and reactions associated with affected compartments (modified from Tretter et al).…”
Section: Dynamic Equilibrium Modelsmentioning
confidence: 89%
“…The potential relationship between chronic distress or type 2 allostasis and the severity of COVID‐19 is still understudied, and methodological problems hamper scientific progress in this intersection. It is, however, well understood that elevated sympathetic activity (and parasympathetic hypoactivity), hyperglycaemia and immune‐dysregulation are markers of a poor outcome; and potential pathophysiological mechanisms underlying this relationship have been identified 79–84 . If confirmed by carefully‐planned prospective studies, these insights may help to prevent an unfavourable outcome of the disease; and they may also explain the conundrum of bio‐social disparities in the prognosis of COVID‐19 85–87 …”
Section: Systemic Physiology and Pathologymentioning
confidence: 99%
“…Nevertheless, an imbalance of the autonomic nervous system has been suggested to determine the severity of Covid-19 20,27 . What is more, the data from the study of He et al 28 provided an important contribution to this notion; since they are considered within the context of the precise pathophysiology underlying the relationship between Covid-19 infection and day-to-day BP variability 7 . In line with this understanding, Li et al 6 observed greater variability of systolic arterial pressure in critically ill patients, when compared with their severe and discharged counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, an autonomic nervous system imbalance has been suggested to determine the severity of COVID-19 (32,42). Moreover, the data from the study of He et al (43) provided an essential contribution to this notion; they are considered within the context of the precise pathophysiology underlying the relationship between COVID-19 infection and day-to-day BP variability (19). In line with this understanding, Li et al (17) observed more significant systolic arterial pressure variability in critically ill patients when compared with their severe and discharged counterparts.…”
Section: Analysis Of Arterial Pressure Variabilitymentioning
confidence: 99%
“…Until now, few reports have assessed the relationship between day-to-day blood pressure variability and mortality in COVID-19 (4,16). In addition to strict blood pressure control, it might be important to minimize day-to-day blood pressure variability to reduce mortality in COVID-19 patients (19).…”
Section: Introductionmentioning
confidence: 99%